Applying the Creative Process to Library Branding - Kellie Sparks (Marketing Libraries Journal, 2017)
How does one cultivate creative inspiration on demand and sustain it over the life of a project? As a library marketing professional, it can be challenging to sustain creativity when crafting ideas to establish or re-envision a library brand. This article examines the creative process with the goal of deepening understanding of how to build a sustainable infrastructure of creativity. This infrastructure is designed with an awareness of the science behind creative thought and significant creativity research. We explore how brain behavior enhances the creative process and can essentially help create a more inspiring library brand. This article provides best practices and tips from creativity experts such as maintaining daily activities including movement, meditation, and reflective thought, to enhance one’s creative prowess while engaged in a library branding project. It also serves as a valuable reminder that creative thought is available for everyone and is not just limited to artists or musicians.